Inovasi digital dalam sistem perpajakan: Pengaruh digitalisasi dan literasi digital terhadap kepatuhan wajib pajak di Kabupaten Manggarai - Gabrini Anggojo Jebarus; Ratih Dewi Titisari Haryana (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2026)
This study aims to examine how digital literacy and digitalization affect taxpayer compliance in Manggarai Regency, one of many regions in Indonesia where tax compliance remains a significant challenge. A quantitative approach with a descriptive-associative design was used. A total of 136 respondents were selected through purposive sampling from individual taxpayers and business entities registered at the Ruteng Tax Office (KPP Pratama). A five-point Likert-type questionnaire was used to collect data, and then occasionally using a number of linear regression models with Statistical Program for Social Science (SPSS) version 27. The results showed that digitalization of the tax system had a positive and significant effect on taxpayer compliance. Similarly, digital literacy had a positive and significant effect on taxpayer compliance, with digital literacy emerging as the dominant variable, explaining 36.4% of the variance. These results indicate that for digital transformation in tax settlement, two things are needed, capable digital facilities and improving the digital capabilities of taxpayers.